Ellagic Acid Alleviates Rheumatoid Arthritis in Rats through Inhibiting MTA1/HDAC1-Mediated Nur77 Deacetylation - Huanjin Song; Hao Wu; Jun Dong; Sihua Huang; Jintao Ye; Ruoxi Liu (Mediators of Inflammation)
Ellagic acid (EA) was reported to play protective roles in rheumatoid arthritis (RA). It was found that the level of metastasis-associated gene 1 (MTA1)/histone deacetylase 1 (HDAC1) protein complex was downregulated by polyphenols in several human disorders. Notably, inhibition of MTA1 or HDAC1 has anti-inflammatory effects on RA. Therefore, our study is aimed at investigating whether EA prevents RA progression through regulating the MTA1/HDAC1 complex. Herein, the human fibroblast-like synoviocyte (FLS) cell line MH7A was treated with TNF-α to induce an inflammation model in vitro and then incubated with different concentrations of EA. Western blot analysis showed that EA reduced MTA1 expression in a dose-dependent manner in MH7A cells. Then, TNF-α-treated MH7A cells were incubated with EA alone or together with MTA1 overexpression plasmid (pcDNA-MTA1), and we found that EA inhibited proliferation, inflammation cytokine levels, and oxidative stress marker protein levels and promoted apoptosis in MH7A cells, while MTA1 overexpression abolished these effects. Moreover, coimmunoprecipitation assay verified the interaction between MTA1 and HDAC1. EA downregulated the MTA1/HDAC1 complex in MH7A cells. MTA1 knockdown inhibited proliferation, inflammation, and oxidative stress and promoted apoptosis in MH7A cells, while HDAC1 overexpression reversed these effects. Moreover, chromatin immunoprecipitation assay indicated that EA inhibited HDAC1-mediated Nur77 deacetylation. Rescue experiments demonstrated that Nur77 knockdown reversed the effects of EA on MH7A cell biological behaviors. Additionally, EA treatment attenuated arthritis index, paw swelling, synovial hyperplasia, and inflammation in collagen-induced arthritis (CIA) rats. In conclusion, EA inhibited proliferation, inflammation, and oxidative stress and promoted apoptosis in MH7A cells and alleviated the severity of RA in CIA rats though downregulating MTA1/HDAC1 complex and promoting HDAC1 deacetylation-mediated Nur77 expression.